Effect of Fibre-Enriched Orange Juice on Postprandial Glycaemic Response and Satiety in Healthy Individuals: An Acute, Randomised, Placebo-Controlled, Double-Blind, Crossover Study - Bosch-Sierra, Neus (Nutrients, 2019)
Background: Consumption of fibre-enriched orange juice may be an appropriate way to supplement daily fibre intake and achieve beneficial effects on metabolic health. The present study aimed to assess the short-term effects of fibre-enriched orange juice on postprandial metabolism and satiety in a healthy adult population. Methods: In this double-blind, randomised, placebo-controlled, crossover study 10 healthy subjects underwent two one-day trials in which they consumed an orange juice beverage containing 1.4 g/100 mL of citrus fibre (29.3% soluble and 41.9% insoluble) or a placebo (regular orange juice without added fibre). Postprandial glucose, insulin, gut hormones (GLP1, GIP and ghrelin), leptin and qualitative appetite/satiety assessment were measured every 15 or 30 min over the 120 min test period. Results: The fibre-enriched orange juice decreased postprandial serum glucose and circulating insulin levels at 15 min compared with the placebo. In addition, after intake of the fibre-enriched juice, a significant effect on qualitative feelings of satiety and fullness was observed at 15 and 120 min, and was accompanied by a significant decrease in GLP1 response at 15 min. No significant changes were observed in leptin, GIP and ghrelin after juice intake. Conclusions: In healthy individuals, a single acute consumption of fibre-enriched orange juice has short-term beneficial effects on postprandial glycaemia, circulating insulin levels and satiety through GLP1 secretion.